Mystery machine: the complex roles of NLRX1 in viral infection - Woolls, Mackenzie K.; Elliott, Carley M.; Ivester, Hannah M.; Allen, Irving Coy (Frontiers in Immunology, 2025)
Effective antiviral immunity requires a delicate balance between controlling infection and preventing excessive inflammation. NLRX1, an atypical member of the NOD-like receptor family, plays a crucial regulatory role in this process by modulating immune responses to both RNA and DNA viruses. Unlike other NLRs, NLRX1 does not directly activate inflammatory pathways, but rather fine tunes immune responses through interactions with key signaling initiators like MAVS, FAF1, viral RNA, and FBXO6. These interactions allow NLRX1 to influence antiviral pathways in a highly context-dependent manner. In RNA virus infections, NLRX1 can either enhance immune signaling to restrict viral replication or suppress type 1 IFN responses to promote viral persistence. Similarly, in DNA viral infections, NLRX1 exerts either protective or pathogenic effects, though the precise mechanisms remain unclear. Emerging evidence suggests that NLRX1 may also serve as a key regulator of inflammation and metabolic processes during infection, further contributing to its complex role in immunity. By synthesizing current research, this review provides insight into how NLRX1 regulates immune signaling in RNA and DNA viral infections, highlighting its dynamic role in antiviral immunity and the remaining gaps in our understanding.